NiOX/MoO3 Bi‐Layers as Efficient Hole Extraction Contacts in Organic Solar Cells. (18th November 2013) - Schulz, Philip; Cowan, Sarah R.; Guan, Ze‐Lei; Garcia, Andres; Olson, Dana C.; Kahn, Antoine
Abstract : The electronic structure of a bi‐layer hole extraction contact consisting of nickel oxide (NiO x ) and molybdenum trioxide (MoO3 ) is determined via ultraviolet and X‐ray photoemission spectroscopy. The bi‐layer presents ideal energetics for the extraction of holes and suppression of carrier recombination at the interface. The application of the NiO x /MoO3 bi‐layer as the anode of organic bulk heterojunction solar cells based on PCDTBT/PC71 BM leads to improved device performance, which is explained by an intricate charge transfer process across the interface. Abstract : Nickel oxide/molybdenum oxide bi‐layers enhance hole collection in organic photovoltaic devices . Device improvement in PCDTBT:PC71BM based solar cells is attributed to the electronic structure of the oxide interlayer. The electron blocking capability of NiO x is combined with the high work function of MoO3, which enable efficient coupling of the electrode to the hole transport level in the polymer.